Role of Logistics in the Development of Agriculture of Ukraine in the War Conditions - Kryshtal, H. (Science and Innovation, 2024)
Introduction. For solving the problem of agricultural development in the context of hostilities on the territory of the state, logistics have been gaining dominance, and its role has been conceptually understudied. Problem Statement. The trajectory of agricultural development in Ukraine today is turbulent because of hosti lities on the territory of the state, so logistics plays one of the key roles. Purpose. The purpose of this research is to determine the role of logistics in the economic development of agriculture in the current conditions of the war in Ukraine. Material and Methods. We have employed the synthesis methods; the analysis has been made with the use of a two-step least squares method and a model with fixed effects, the method of historical and logical modeling, the method of “from abstract to concrete,” the method of economic and mathematical modeling, and economic interpretation. From a practical point of view, we also have employed the method of grouping statistical data, statistical and econometric analysis, and the graphical method. Results. The concepts of logistics and agrologistics have been considered, and the logistics of grain crops by railway, road, and river transport have been analyzed. The results of the study have revealed the trends that made it possible to identify the areas for the development of agriculture in Ukraine during the war, namely: increasing the amount of sown areas; increasing the number of jobs for rural residents; introducing (cultivating, purchasing) new varieties of crops; improving the quality of cultivated land; purchasing modernized equipment for processing, storage, and logistics of grain crops; increasing the grain harvest that may be exported in the future. Conclusions. The directions for agricultural development of Ukraine in the conditions of the war have been determined. It has been proven that the effect of the outlined directions is impossible unless the appropriate measures for the development of logistics and the grain market in the country are introduced. The proven connection between “logistics — grain market — development of agriculture” characterizes the micro- and macroeconomic effects of this interaction and reflects the role of the socio-economic development of the state in this process.